2001
DOI: 10.1021/ic000313v
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Crystal Structure, Spectral Studies, and Catechol Oxidase Activity of Trigonal Bipyramidal Cu(II) Complexes Derived from a Tetradentate Diamide Bisbenzimidazole Ligand

Abstract: A new benzimidazole-based diamide ligand-N,N'-bis(glycine-2- benzimidazolyl)hexanediamide (GBHA)-has been synthesized and utilized to prepare Cu(II) complexes of general composition [Cu(GBHA)X]X, where X is an exogenous anionic ligand (X = Cl(-), NO(3)(-), SCN(-)). The X-ray structure of one of the complexes, [Cu(GBHA)Cl]Cl.H(2)O.CH(3)OH, has been obtained. The compound crystallizes in the monoclinic space group C2/c with unit cell dimensions a = 26.464(3) A, b = 10.2210(8) A, c = 20.444(2) A, alpha = 90 degre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(62 citation statements)
references
References 46 publications
3
57
0
2
Order By: Relevance
“…The broad shape of this band suggests the existence of H-bonds. The intense bands in the region of 1,637-1,518 cm -1 can be assigned to m s (C-O), r(NH), m s (C=N) and m as (C=N) which indicate the deprotonation through thioenolization on coordination [32], plus the pyridine ring vibrations. Coupled vibrations among the thioamide bands are distributed around 1,437 and 1,361 cm -1 with two equal bands.…”
Section: Ir Spectramentioning
confidence: 99%
“…The broad shape of this band suggests the existence of H-bonds. The intense bands in the region of 1,637-1,518 cm -1 can be assigned to m s (C-O), r(NH), m s (C=N) and m as (C=N) which indicate the deprotonation through thioenolization on coordination [32], plus the pyridine ring vibrations. Coupled vibrations among the thioamide bands are distributed around 1,437 and 1,361 cm -1 with two equal bands.…”
Section: Ir Spectramentioning
confidence: 99%
“…Dinuclear copper complexes with Cu-Cu separation of $3 Å are interesting as corroborative model of the active site of catechol oxidase to elucidate the functional mechanism of the native enzyme and to develop bio-inspired catalytic systems [1][2][3][4][5][6][7][8][9]. When that separation is associated with bridging azido ligand the species becomes of particularly interesting for gaining deeper insight into magneto-structural correlation, a study very much essential for developing new functional molecule based materials [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…We believe that a similar mechanism may be operative in our case also. Earlier we have found that similar, bis-benzimidazole copper(II) complexes, also catalyze reactions by the hydrogen abstraction mechanism [11,13].…”
Section: Epr Spectroscopy and Cyclic Voltammetrymentioning
confidence: 96%
“…of commercially available TBHP. Earlier, we have initiated a study of copper(II) complexes utilizing bis benzimidazole diamide ligands, as oxidants towards a variety of substrates [11][12][13].…”
Section: Introductionmentioning
confidence: 99%